HEADACHE MANIFESTATION OF COVID-19: A CASE SERIES AND NARRATIVE REVIEW - Rizaldy Taslim Pinzon; Nunki Puspita Utomo; Gabriel Pramono Btara Yudhitia (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Despite the typical primary symptoms reported, the coronavirus disease 2019 (COVID-19) outbreak could be manifested as many symptoms. Neurological manifestations of COVID-19 are hypothesized to be caused by multiple pathophysiologies. As one of the possible prodromal symptoms in the absence of fever and respiratory symptoms, many individuals might be unaware of contracting COVID-19 infection and could possibly infect other people. This case series involved a hundred and twenty COVID-19 patients in which nine of them reported headaches as the chief complaint to provide the prevalence rate. Medical histories were assessed to provide the prevalence rate and laboratory findings of involved subjects. Narrative review of possible mechanisms of the manifestation were also denoted. To date, the proportion of non-specific manifestations as the first symptom needs to be further explored as it could be one of the initial symptoms and early manifestations of COVID-19.